Detailed investigation of defect states in Erbium doped In2O3 thin films - Henini, M. (Elsevier, 2018)
Erbium doped Indium Oxide (In2O3:Er) thin films (TFs) were synthesised by spin-on technique. Secondary Ion Mass Spectrometry confirmed that Er is incorporated into the In2O3 lattice and formed an In-O-Er layer. The current–voltage loop produced a lower loop current window of ∼3.6 × 10−4 A for In2O3:Er TF based devices. The Au/In2O3:Er/Si Schottky devices have lower ideality factor (∼6) and higher barrier height (∼0.63 eV) at 300 K than Au/In2O3/Si control samples. A blue shift in the main band-gap (∼50 nm) was calculated for In2O3:Er TFs from 10 K photoresponse. The Au/In2O3:Er/Si samples show higher photosensitivity in the temperature range 10 K–300 K and maximum (∼15 times) in the UV region at 10 K as compared to the Au/In2O3/Si devices. In addition, the Au/In2O3:Er/Si devices have better UV to visible cut-off ratio (∼3 times). Excellent temporal responses were recorded for Au/In2O3:Er/Si in the UV region as compared to Au/In2O3/Si.